Amirudin Tamoreka’s Strategy In Innovating Personal Branding To Maintain His Image as Incumbent Regent In The 2024 Banggai Regional Election - Setiadi, Muh. Darmawan (Green Publisher Indonesia, 2025)
This research aims to analyze Amirudin Tamoreka's personal branding strategy in maintaining his image as an incumbent in the 2024 Banggai Regional Election. As a candidate who is running for re-election, Amirudin adopts a polite, communicative, and innovative political approach by prioritizing ethical values and real work. This study uses a qualitative method with a case study approach, with the main informants consisting of the figure of Amirudin Tamoreka, the winning team, and the chairman of the supporting party. The findings of the study show that Amirudin has succeeded in building a strong personal branding based on the eight principles from The Laws of Personal Branding theory by Peter Montoya, namely specialization, leadership, personality, difference, consistency, unity, constancy, and goodwill. The branding strategy carried out through social media, a humanist approach, and real proof of work during the first period, made his image remain positive in the eyes of the public. His success was evidenced by his victory in the 2024 Regional Elections despite facing challenges in the form of negative issues from political opponents. This research shows that planned and authentic personal branding is able to influence public perception and increase the electability of incumbents in local political contests.